Local Immigration Enforcement and Local Economies. Issue 2 (April 2017) - Bohn, Sarah; Santillano, Robert
Abstract : We examine the impacts of a locally enforced immigration program—287(g)—on private employer reports to the Quarterly Census of Employment and Wages. Using contiguous‐county pairs to account for time‐varying local economic shocks, we identify impacts on immigrant‐intensive industries that are robust to prepolicy time trends, implementation timing, and the exclusion of pairs with large prepolicy differences. Reported employment was 4 percent higher in manufacturing, but 7–10 percent lower in administrative services. These results are consistent with adverse labor‐supply shocks, and, to a lesser extent, a decline in labor demand for locally produced goods and services.